Physico-Chemical and Metallic Characterization of Industrial Effluent and Nearby Well Water in Pen Region, Dist. Raigad, Maharashtra - Sonawane, V.Y. (Asian Journal of Chemistry, 2012)
The paper presents the results on physico-chemical studies of different water and industrial samples of highly polluted industrial area of Pen. The author has analyzed the samples for water quality parameters like colour, pH, total hardness (TH), chlorides (Cl-), calcium (Ca), magnesium (Mg), acidity, alkalinity, COD, BOD, Na, Cu, Cd, Pb, Fe etc. For the impact assessment of industrial wastes some nearby soil and ground water samples were also analyzed. The results are being discussed in the light of pollution status of the area and literature on public health aspects.